2020
DOI: 10.1002/cphc.202000923
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Hückel and Möbius Aromaticity in Metal‐Metal Quintuple Bonded Complexes of Cr, Mo, and W with Amidinate Ligand: Ab initio DFT and Multireference Analysis**

Abstract: The aromaticity of metal‐metal quintuple bonded complexes of the type M2L2 (M=Cr, Mo, and W; L=amidinate) are studied employing gauge including magnetically induced ring current (GIMIC) analysis and electron density of delocalized bonds (EDDB). It is found that the complexes possess two types of aromaticity: i) Hückel aromaticity through delocalization of ligand π electrons with metal‐metal δ‐bond‐forming 6 conjugated electrons (4π and 2δ) ring; ii) Craig‐Möbius aromaticity through delocalization of π electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Thus, to gain more insight into aromaticity/antiaromaticity/nonaromaticity the ring current calculations were performed using the GIMIC method. [74][75][76] The clockwise current (positive current) is called the diatropic current, and the anticlockwise current (negative current) is termed the paratropic current. The ring currents were calculated using the Gauss quadrature method in a cross-section area of a molecule.…”
Section: Aromaticity Analysis I Nucleus Independent Chemical Shift (N...mentioning
confidence: 99%
“…Thus, to gain more insight into aromaticity/antiaromaticity/nonaromaticity the ring current calculations were performed using the GIMIC method. [74][75][76] The clockwise current (positive current) is called the diatropic current, and the anticlockwise current (negative current) is termed the paratropic current. The ring currents were calculated using the Gauss quadrature method in a cross-section area of a molecule.…”
Section: Aromaticity Analysis I Nucleus Independent Chemical Shift (N...mentioning
confidence: 99%
“…In general, for aromatic molecules, the clockwise (diatropic) current is present outside the ring, and the anticlockwise current (paratropic) is present inside the ring. In previous works [78–82], we have shown that it is a compelling technique for the analysis of aromaticity. Here also, we have employed the GIMIC method to calculate the ring current across various bonds at the TS structures of all four reactions (Table 5, Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Möbius aromaticity arises when there is a phase shift in the molecule. This can be achieved in two ways [78]: (i) through nuclear arrangement (a twist in the molecule), and Heilbroner type; (ii) through orbital arrangement, Craig type. Here the molecules are showing Craig type Möbius aromaticity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations